The Role of Consumer Knowledge Towards Country of Origin Cues of Australian Wines - Cheah, Isaac; Phau, Ian (Australian and New Zealand Marketing Academy, 2012)
This paper investigates the effects of country-of-origin (COO) cues, economic nationalism and consumer ethnocentrism on product judgment by considering the role of product knowledge with an Australian sample. The results indicated that country of origin cues affect Australian consumers in wine evaluations despite its weak influences. It suggested that the effect of country of origin in product judgment with low product knowledge is greater than in those with high product knowledge. However, the study also found inconsistent results between different country of origin of manufacture and country of origin of ownership cues and its effects on product judgment of bi-national brands (unfamiliar and more complex brands).